Influence of different 1v1 small-sided game conditions in internal and external load of U-15 and U-12 soccer players - Santos, Fernando Jorge; Caldeira Ferreira, Cátia; Figueiredo, Teresa Palmira; Cunha Espada, Mário (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Soccer is a complex team sport, in which moments of 1v1 during the game may decide the outcome. Despite this evidence, studies on this particularity are scarce, particularly involving young players. Aim of Study. The purpose of this study was to evaluate variations of internal and external loads in U-15 and U-12 soccer players associated to different smallsided game (SSG) conditions, in the 1v1 context. Material and Methods. Eight male soccer players participated in the study, integrating two groups, U-15 (n = 4) and U-12 (n = 4), monitored in different SSG models (2 minutes duration / 3 minutes interval rest, different pitch size SSG1 = 5 × 10 m; SSG2 = 10 × 15 m; SSG3 = 15 × 20 m). Soccer players carried GPS devices (WIMU PROTM, RealTrack System, Almería, Spain) operating at a sampling frequency of 10 Hz. The Mann–Whitney U test was used to compare groups in each SSG and the Kruskal–FWallis test was applied to compare the different SSGs. The significance level was adopted at p < 0.05. Results. Differences between the groups were observed mostly in HRmean and HR95-max. The distance covered (different between the groups, SSG1 197.7 ±14.0 vs 162.3 ± 9.0 and SSG3 261.4 ± 10.6 vs 217.1 ± 27.4, respectively, for U-15 and U-12) and maximal velocity always increased with the increase of the pitch size. Explosive distance and accelerations were also different between the groups in SSG1 and SSG2, respectively. Differences throughout the SSGs were mainly recorded in terms of external load. Conclusions. This research suggests that the implemented 1v1 SSG model is relevant from the internal and external load perspective. Nevertheless, the internal and external loads in U-15 and U-12 soccer players present differences and specificities, which should be considered in exercise prescription and individualized evaluation of young soccer players.
Keywords: soccer; internal load; young players; external load; small-sided game